2015
DOI: 10.1111/jgh.12812
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of trinitrobenzene sulfonic acid‐induced colitis in mice by liquiritigenin

Abstract: Liquiritigenin may ameliorate TNBS-induced colitis in mice by suppressing expression of pro-inflammatory cytokines through NF-κB pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 46 publications
(70 reference statements)
2
6
0
Order By: Relevance
“…Our result showed that LPS treatment significantly induced IL-1β, IL-6 and TNF-α accumulation and immune cell infiltration, which could be effectively inhibited by LIQ treatment. This was consistent with previous studies that showed that LIQ exerts its antiinflammatory effect in several disease models via inhibiting the NF-κB and NLRP3 inflammasome pathways (Min et al, 2015;Yu et al, 2015;Hongyan et al, 2016). We confirmed here that LIQ treatment could inhibit IκB/NF-κB signaling, which was in agreement with previous studies.…”
Section: Discussionsupporting
confidence: 94%
“…Our result showed that LPS treatment significantly induced IL-1β, IL-6 and TNF-α accumulation and immune cell infiltration, which could be effectively inhibited by LIQ treatment. This was consistent with previous studies that showed that LIQ exerts its antiinflammatory effect in several disease models via inhibiting the NF-κB and NLRP3 inflammasome pathways (Min et al, 2015;Yu et al, 2015;Hongyan et al, 2016). We confirmed here that LIQ treatment could inhibit IκB/NF-κB signaling, which was in agreement with previous studies.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, treatment of colitic animals with p-C-rich medicinal species also decreased pro-inflammatory cytokines IL-1β, IL-6, GM-CSF, and TNFα mRNA levels [43]. Similar immunomodulatory effects have been shown for polyphenol paeoniflorin and flavonoid liquiritigenin [49,74].…”
Section: Discussionsupporting
confidence: 54%
“…Liquiritigenin is a flavonone from licorice , the dried root of Glycyrrhiza glabra . It exhibits estrogenic [ 16 ], choleretic [ 17 ], anti-inflammatory [ 18 ], and antitumor [ 19 ] effects. This study investigates the effect of liquiritigenin on CCl4-induced chronic liver injuries and the biochemical pathways involved.…”
Section: Introductionmentioning
confidence: 99%